Kemampuan Menulis Puisi Baru dalam Bahasa Makassar Siswa Kelas VIII SMPN 1 Takalar - Nur Annisa Maulina Natsir; Kemong Daeng; Hajrah Hajrah; Andi Agussalim; Aswati Asri (HUMAN: South Asian Journal of Social Studies, 2023)
Abstract.This study aims to describe the ability to write new poetry in Makassar language through audiovisual media for class VIII students of SMPN 1 Takalar. The population in this study were all 256 grade VIII students of SMPN 1 Takalar, Takalar Regency, spread across 8 classes. The sample was determined as many as 33 students of SMPN 1 Takalar, Takalar Regency. The type of sampling used is cluster random sampling. This research was conducted twice with research subjects namely class VIII-A students, totaling 33 people, carried out in an odd semester, on March 13 and March 20 2023 to be precise using data collection techniques in the form of performance tests (writing poetry, while analysis techniques the data used is descriptive statistics. The results of the research on the ability to write new poetry in Makassar have reached the criterion of 75%. which shows that the sample that got a score of 75-100 totaled 26 students (78.8%) and the sample that got a score of 0-74 totaled 7 students (21.2%) This shows that the ability to write new poetry in Makassar class VIII students of SMP Negeri 1 Takalar Takalar Regency were declared capable.Keywords: New Poetry, Writing Skill, Makassar Language, Local Language